An Assessment of the Organizational Culture Change on Organizational Performance - Josee, Veronese Marie; Shisia, Adam (My University, 2014)
Culture change has indeed become an imperative for organizational competitiveness and effectiveness. Forces like globalization and internationalization of public issues contribute to expanding the flow of labour across national boundaries and facilitate constant exchange of materials, as well as culture change. The purpose of this study was to establish the effect of organizational culture change on organizational performance using the Kenyan Immigration Department as a case study. The objective of the study was to find out how the organizational culture change affects public sector organizations in developing countries using the Kenyan experience.The research methodology adopted a descriptive survey design and the study used both quantitative and qualitative data that described cultural change at the immigration department of Kenya in Nairobi. The study collected both primary and secondary data. Primary data was gathered using structured and semi-structured questionnaires where the respondents were issued with the questionnaires to respond to questions.The study established that a culture change acts as a driving force of development in an organization and leads to a more fulfilling intellectual, emotional, moral and spiritual life. It helps to improve the organization's performance in the marketplace. It also came to the researcher’s attention that most of the organization did not engage staff members fully in promoting togetherness in the work environment, and that the identity has played a functional role in the organizational culture among employees from diversified groups to a great extent. The study recommended that organizations should improve their organizational culture in order to properly manage workplace diversity so as to improve performance. This will encourage teamwork in the organization and enhance organizational performance. The study further recommended that the organizations should streamline internal communication in order to enhance performance.
Keywords: Culture change; Workplace culture change; Organizational performance